Penerapan Data Mining Untuk Estimasi Penjualan Obat Berdasarkan Pengaruh Brand Image Dengan Algoritma Expectation Maximization (Studi Kasus: PT. Pyridam Farma Tbk) - Nainel, Yane Laheroi; Buulolo, Efori; Lubis, Ikwan (STMIK Budi Darma, 2020)
Data mining, often also called knowledge discovery in database (KDD), is an activity that includes the collection, use of historical data to find regularities, patterns or relationships in large data sets. The output of data mining can be used to improve decision making in the future. PT. Pyridam Frama Tbk is a multi-national company that produces pharmaceuticals. The problems that often occur at PT Pyrida Farma are estimation problems such as out of stock of goods at distributors, lack of labor, running out of raw materials at the factory. Another problem contained in the agency is that it does not yet have a system to predict the estimated drug sales each year, so we need an algorithm, the Expectation Maximization Algorithm. then with this made the Application of Data Mining for Estimating Drug Sales Based on the Effect of Brand Image. Expectation Maximization algorithm which is a method that supports in estimating or predicting sales target estimates for the coming period. Algorithm testing is done using SPSS and MYSQL software. From the results of research that has been done it can help the PT. Pyridam Farma to make it easier to predict drug sales estimates by using SPSS Software